2023
DOI: 10.3390/ijms24021244
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic Drug Resistance Associated with Differential miRNA Expression of miR-375 and miR-27 among Oral Cancer Cell Lines

Abstract: Recent advances have suggested that non-coding miRNAs (such as miR-21, miR-27, miR-145, miR-155, miR-365, miR-375 and miR-494) may be involved in multiple aspects of oral cancer chemotherapeutic responsiveness. This study evaluated whether these specific miRNAs are correlated with oral cancer responsiveness to chemotherapies, including Paclitaxel, Cisplatin and Fluorouracil (5FU). Commercially available and well-characterized oral squamous cell carcinoma cell lines (SCC4, SCC9, SCC15, SCC25 and CAL27) revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…The primary objective of this current study was to provide an evaluation of the specific microRNA expression profile of the oral cancer cell line SCC15 lacking chemotherapeutic resistance, which may provide new potential insights into potential treatments and therapies. These results confirmed the upregulation of miR-145 among this chemosensitive cell line previously reported by this group [47]. This supports other research that demonstrates that the downregulation of miR-145 expression was associated with oral cancer diagnosis and progression, while miR-145 upregulation correlated with improved prognosis and increased survival [31,39].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The primary objective of this current study was to provide an evaluation of the specific microRNA expression profile of the oral cancer cell line SCC15 lacking chemotherapeutic resistance, which may provide new potential insights into potential treatments and therapies. These results confirmed the upregulation of miR-145 among this chemosensitive cell line previously reported by this group [47]. This supports other research that demonstrates that the downregulation of miR-145 expression was associated with oral cancer diagnosis and progression, while miR-145 upregulation correlated with improved prognosis and increased survival [31,39].…”
Section: Discussionsupporting
confidence: 92%
“…Recent work from this group has demonstrated the upregulation of miR-21 and miR-365 among oral cancers, as well as the confirmation of the downregulation of miR-27 among chemoresistant oral cancer cell lines [46,47]. Moreover, this most recent study found that the upregulation of miR-145 and the downregulation of miR-155 were also strongly correlated with a lack of chemotherapy resistance, although the mechanism(s) responsible for this observation remained unidentified [47].…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations